2018
DOI: 10.1158/2159-8290.cd-17-0745
|View full text |Cite
|
Sign up to set email alerts
|

A Preexisting Rare PIK3CAE545K Subpopulation Confers Clinical Resistance to MEK plus CDK4/6 Inhibition in NRAS Melanoma and Is Dependent on S6K1 Signaling

Abstract: Combined MEK and CDK4/6 inhibition (MEKi + CDK4i) has shown promising clinical outcomes in patients with -mutant melanoma. Here, we interrogated longitudinal biopsies from a patient who initially responded to MEKi + CDK4i therapy but subsequently developed resistance. Whole-exome sequencing and functional validation identified an acquired mutation as conferring drug resistance. We demonstrate that preexisted in a rare subpopulation that was missed by both clinical and research testing, but was revealed upon mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 33 publications
(37 reference statements)
5
55
0
Order By: Relevance
“…S1G and S1H) and an increase in CCND1 ( Supplementary Fig. S1H) total protein levels, both of which are consistent with previous studies (7,11). Palbociclib inhibition did not alter the MAPK signaling components RAF and MEK, however we did observe an increase in phospho-ERK levels (Fig.…”
Section: Nras-dependent Melanoma Cell Lines Are Sensitive To Pharmacosupporting
confidence: 91%
See 2 more Smart Citations
“…S1G and S1H) and an increase in CCND1 ( Supplementary Fig. S1H) total protein levels, both of which are consistent with previous studies (7,11). Palbociclib inhibition did not alter the MAPK signaling components RAF and MEK, however we did observe an increase in phospho-ERK levels (Fig.…”
Section: Nras-dependent Melanoma Cell Lines Are Sensitive To Pharmacosupporting
confidence: 91%
“…S2D). As there are limited clinical samples available for the evaluation of resistance to this combination (7,8), we used cBioPortal (http://www.cbioportal.org/) to determine whether proteins identified in the ORF overexpression screen were altered either through point mutation or amplification in NRAS-mutant melanoma. We observed that ARAF, KRAS, AKT1, PIK3CA, RAF1, BRAF, and AKT3 were either mutated (hotspot) or amplified in NRAS-mutant melanoma (Fig.…”
Section: Nras-dependent Melanoma Cell Lines Are Sensitive To Pharmacomentioning
confidence: 99%
See 1 more Smart Citation
“…Most qPCR, Sanger, and NGS-based assays and panels for oncology targeted therapy selection [40][41][42] have mutation VAF sensitivities of between 1% and 5%, and thus are unable to identify low VAF drug resistance mutations arising from trace subclones due to tumor heterogeneity. However, under the selective pressures of targeted therapy, tumor subclones with drug resistance mutations can rapidly expand and cause treatment failure or cancer recurrence [43][44][45][46]. Thus, reliable detection of low VAF drug resistance mutations can inform personalized treatment selection, including the use of combination therapies, to improve patient outcomes.…”
Section: Melanoma Mbda Ngs Panel Reveals Frequent Heterogeneity In Tumentioning
confidence: 99%
“…However, all of these studies are still in early-phase clinical trials. Furthermore, primary and acquired resistance to some of the combinations, such as the MEK inhibitor MEK162 with a CDK4/6 inhibitor (18,19), are emerging. Therefore, there is a continued need to understand the mechanism of resistance of NRAS mutant melanomas to MEK inhibitors and to develop new treatment strategies.…”
Section: Introductionmentioning
confidence: 99%